2013
DOI: 10.1213/ane.0b013e31826257f4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Full Expiration on the Position and Size of the Subclavian Vein in Spontaneously Breathing Adults

Abstract: The distance from the SCV to the pleura did not change after full expiration. However, this simple technique can still be considered during placement of subclavian catheters in spontaneously breathing patients, because it significantly enlarges the CSA of the SCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…It has been reported that positive end-expiratory pressure (PEEP) application [ 1 , 3 ], intrathoracic pressure application [ 4 ], Trendelenburg position [ 1 , 4 ], hepatic compression [ 4 ], and valsalva maneuver [ 5 ] increase the CSA of IJV. The CSA of SCV, on the other hand, is reportedly increased by the combined use of inspiratory hold and Trendelenburg position [ 6 ], complete expiration in spontaneously breathing subjects [ 7 ], Trendelenburg position alone [ 8 ], and leg elevation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that positive end-expiratory pressure (PEEP) application [ 1 , 3 ], intrathoracic pressure application [ 4 ], Trendelenburg position [ 1 , 4 ], hepatic compression [ 4 ], and valsalva maneuver [ 5 ] increase the CSA of IJV. The CSA of SCV, on the other hand, is reportedly increased by the combined use of inspiratory hold and Trendelenburg position [ 6 ], complete expiration in spontaneously breathing subjects [ 7 ], Trendelenburg position alone [ 8 ], and leg elevation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent ultrasonographic studies have shown that lung deflation does not reduce the distance between the pleura and subclavian vein in paediatric patients receiving mechanical ventilation and in spontaneously breathing adults [5,6]. Previous studies have investi-…”
Section: Discussionmentioning
confidence: 99%
“…However, recent ultrasonographic studies have shown that lung deflation does not reduce the distance between the pleura and subclavian vein in paediatric patients receiving mechanical ventilation and in spontaneously breathing adults [5,6]. Previous studies have investi-gated only the infraclavicular area, using cross-sectional short-axis images of the subclavian vein but did not image the entire needle pathway including the site at which the subclavian vein is commonly punctured.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on existing exploratory studies using ultrasonography,22 23 20 people were randomly selected for each age group. Categorical data were collated as numbers and percentages and compared using χ² test or Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%